Use of Macro Basalt Fibre Concrete for Marine Applications - Mohammadi Mohaghegh, Ali (KTH, Betongbyggnad, 2016)
Deterioration of concrete structures due to the corrosion of embedded steel is a well-known universal problem. Norway with its numerous bridges, ports, offshore and floating structures along its coastline, is also encountered with corrosion degradation. The harsh environment of the Norwegian Sea regarding its low temperature, wind, and waves, makes the design and construction of marine structures more demanding. In recent years, usage of sustainable composite materials in the field of structural engineering has been rising. The usage of natural fibre reinforced polymer materials in the form of reinforcement bars or macro fibres with a low density, high strength, and excellent corrosion resistance, gives us better choices for the design and construction of marine structures. Our knowledge about the fibre reinforced self-compacting concrete has increased as a result of introducing it as a building material some decades ago. However, more research is still needed when it comes to the application of new types of fibres. This thesis is a result of this need, whereby the author has done two series of experimental programmes regarding the subject. In the first series, the flow characteristics of fresh state, conventional and self-compacting macro basalt fibre concrete were studied. In the second series, mechanical properties of high performance and medium strength macro basalt fibre concrete including the post-cracking behaviour, compressive strength and electrical resistivity were in focus. The findings were presented in three appended papers and the extended summary composing this thesis. Additionally, the thesis presents an overview of the design procedure of floating concrete structures and the possibility of using macro basalt fibre concrete via a case study. The author’s literature review shows that basalt fibres have an adequate resistance against alkali environment of the concrete matrix and corrosive environment of seawater. QC 20160607